An eighty percent pass accuracy may be a critical level on soccer team success - Subak, Erdem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
In this research, the author analyzed the pass accuracy (PA) of center-back (CB), wing-back (WB), center-midfield (CM), wing-midfield (WM) and center-forward (CF) players, and the points of Turkish Super League (TSL) 2020-2021 season. Pearson Correlation Test was used for statistical analysis and confidence interval was settled as 99% (p < 0.01). The results showed that the PA average of CB and CM players was highly related to the points obtained at the end of the season. The passing accuracy of the teams finishing the league in the best places was above 80%, and it was lower in those teams with less points. In conclusion, the results demonstrated that pass accuracy affected the league rank of TSL, and a pass accuracy of 80% may be a critical level to finish in the top ranking of the league.